Methyl-β-cyclodextrin suppresses the monocyte-endothelial adhesion triggered by lipopolysaccharide (LPS) or oxidized low-density lipoprotein (oxLDL) - Guo Chen; Yun Zhou; Wendiao Zhang; Ying Qin; Bo Wei; Yanan Sun; Yong Chen (Pharmaceutical Biology, 2021)
Context Recent studies demonstrated the anti-atherosclerotic efficacy of cyclodextrin. However, it remains unclear whether cyclodextrin exerts the anti-atherosclerotic effect via regulating monocyte-endothelial adhesion. Objective To answer that question by recruiting methyl-β-cyclodextrin (MβCD) as a cyclodextrin representative. Materials and methods Human umbilical vein endothelial cells (HUVECs) were not treated, or treated with 1 µg/mL liposaccharide (LPS) or 50 µg/mL oxidized low-density lipoprotein (oxLDL) for 12 h, 5 mM MβCD for 1 h, and LPS/oxLDL (1 and 50 µg/mL, respectively for 12 h) plus MβCD (5 mM for 1 h), respectively. The effects of MβCD on LPS/oxLDL-triggered monocyte-endothelial adhesion and related molecules in signalling pathways were evaluated via confocal microscopy, flow cytometry, RT-PCR, western blotting, and cell adhesion assay. Results MβCD with an IC50 of 27.66 mM (1 h treatment) exerted no significant cytotoxicity at ≤5 mM for ≤2 h. Compared with the control, both LPS and oxLDL induced an ∼2–3-fold increase in adhesion molecule expression (ICAM-1 and VCAM-1 at protein and mRNA levels) and NF-κB phosphorylation (p-NF-κB/pP65), an increase in IκB kinase (IKK), and a decrease in phosphorylated protein kinase B (p-Akt), respectively. Moreover, more monocytes (2-fold higher for LPS and 15% higher for oxLDL) were attached on LPS/oxLDL-stimulated HUVECs. 5 mM MβCD reversed the LPS/oxLDL-induced changes back to the control levels. Conclusions MβCD significantly suppresses the LPS/oxLDL-triggered monocyte-endothelial adhesion by downregulating adhesion molecule expression probably via LPS-IKK-NF-κB or oxLDL-Akt-NF-κB pathway. This study demonstrates a potential mechanism of the anti-atherosclerotic efficacy of cyclodextrin from the angle of monocyte-endothelial adhesion.